A Comparative Analysis of the Advanced Encryption Standard (AES) 128-, 192-, and 256-Bit Algorithms in Digital Data Security - Putra Daffa Dwiyansah; Fiqri Fathurrohman; Nakhwah Alfikry; Jefry Sunupurwa Asri (Jurnal Multidisiplin Sahombu, 2026)
Data security is a crucial aspect of modern information systems as digital data exchange via the internet increases. One widely used solution to protect data confidentiality and integrity is the Advanced Encryption Standard (AES) cryptographic algorithm, which has three main variants based on key length: AES-128, AES-192, and AES-256. This study aims to analyze and compare the security characteristics and performance of these three AES variants based on a literature review of five relevant national journals. The research method used is a literature review with an analysis and synthesis approach to previous research results. The results show a consistent trade-off between security level and computational efficiency. AES-128 excels in speed and resource efficiency, making it suitable for devices with computing limitations. AES-192 offers a balance between performance and security, while AES-256 provides the highest level of security at the expense of increased processing time and resource usage. The conclusion of this study emphasizes that the selection of an AES variant must be tailored to system requirements and data sensitivity levels, and opens up opportunities for further research related to optimizing AES implementation, particularly in modern web application environments.